Complete genome sequence and anti-obesity potential of Lactiplantibacillus plantarum HOM2217 in 3T3-L1 cells and high-fat diet-fed rats - Wang, Tingting; Zhang, Xiao; Fan, Linlin; Zhao, Ying; Zhang, Zhengwen; Cao, Zhonghua; Xu, Ying; Lee, Suwon; Lim, Chongyoon; Zhang, Shiqi (Frontiers in Microbiology, 2024)
The global prevalence of obesity is rising year by year, which has become a public health problem worldwide. Many animal and clinical studies have shown that Lactiplantibacillus plantarum is considered an ideal probiotic and potential supplement for the treatment of obesity. In this study, we aimed to complete the genome sequence of L. plantarum HOM2217, which was isolated from human milk, and study its physiological characteristics and anti-obesity effects in 3T3-L1 cells and rats fed a high-fat diet (HFD) to determine its potential as a starter for functional food products. Wholegenome analysis demonstrated that HOM2217 contained a single circular chromosome of 3,267,529 bp with a GC content of 44.5% and one plasmid (62,350 bp) with a GC content of 38.5%. Compared to the reference strains, HOM2217 demonstrated superior tolerance to gastrointestinal conditions, higher adhesion to intestinal epithelial cell lines, potent antimicrobial activity against Enterobacter cloacae ATCC 13047, and effective cholesterol removal ability in vitro. Treatment with heat-killed HOM2217 significantly reduced lipid accumulation and intracellular triglyceride production in 3T3-L1 adipocytes. Daily treatment of HFD-fed rats with HOM2217 for 7 weeks decreased body weight, body weight gain, and body fat without changes in food intake. HOM2217 also significantly increased the serum high-density lipoprotein cholesterol (HDL-C) level, decreased the serum tumor necrosis factor (TNF-α) and increased short-chain fatty acid (SCFA) (formic acid, acetic acid, and butyric acid) levels in the cecum. Thus, HOM2217 could potentially prevent obesity in rats by inhibiting inflammatory responses and regulating lipid metabolism and SCFAs expression. Therefore, HOM2217 has potential as an alternative treatment for obesity.